Penerapan Model Pembelajaran SQ3R (Survey, Question, Read, Recite and Review) untuk Meningkatkan Hasil Belajar Siswa Pada Pelajaran Ekonomi Kelas XI MA DA Jerowaru: Implementation of the SQ3R Learning Model (Survey, Question, Read, Recite and Review) to Improve Student Learning Outcomes in Economics Lessons for Class XI MA DA Jerowaru - Sukranudin (Pendidikan Al-Gafari, 2025)
The world of education has a fairly large important role in developing people's lives towards a better future. This study aims to determine how much influence the application of the SQ3R learning model (Survey, Question, Read, Recite and Review) has on Improving Student Learning Outcomes in Economics Class XI MA DA Jerowaru. The SQ3R learning model is a strategy for reading texts containing written lesson materials to be read, either in the form of textbooks or other books related to the subject. Student learning outcomes are students' abilities after receiving their learning experiences. This study is a classroom action research (CAR) using the SQ3R learning model involving 30 students in class XI MA DA Jerowaru, in this study consisting of two cycles, each cycle consisting of planning, implementation, observation and reflection. In cycle I, the number of students who completed was 20 people with a classical completion percentage of 66.67% which is still categorized as low. And in cycle II, the number of students who completed was 26 people with a classical completion percentage of 86.67%. This result has exceeded the classical completeness standard that has been determined, which is 85%. Likewise with the results of observations of student learning activities, in cycle I it was obtained that 0% of students were categorized as very active, 70% of students were categorized as active and 30% of students were categorized as quite active, while in cycle II it was recorded that 7% of students were categorized as very active, 83% of students were categorized as active and 10% of students were categorized as quite active. Based on the research data, it can be concluded that the application of the SQ3R (Survey, Question, Read, Recite and Review) learning model plays a role in student learning outcomes, in an effort to improve the quality of education.